The incidence and clinical burden of respiratory syncytial virus disease identified through hospital outpatient presentations in Kenyan children. - Emelda A Okiro; Mwanajuma Ngama; Ann Bett; D James Nokes (PLoS ONE)
Background There is little information that describe the burden of respiratory syncytial virus (RSV) associated disease in the tropical African outpatient setting. Methods We studied a systematic sample of children aged <5 years presenting to a rural district hospital in Kenya with acute respiratory infection (ARI) between May 2002 and April 2004. We collected clinical data and screened nasal wash samples for RSV antigen by immunofluorescence. We used a linked demographic surveillance system to estimate disease incidence. Results Among 2143 children tested, 166 (8%) were RSV positive (6% among children with upper respiratory tract infection and 12% among children with lower respiratory tract infection (LRTI). RSV was more likely in LRTI than URTI (p<0.001). 51% of RSV cases were aged 1 year or over. RSV cases represented 3.4% of hospital outpatient presentations. Relative to RSV negative cases, RSV positive cases were more likely to have crackles (RR = 1.63; 95% CI 1.34-1.97), nasal flaring (RR = 2.66; 95% CI 1.40-5.04), in-drawing (RR = 2.24; 95% CI 1.47-3.40), fast breathing for age (RR = 1.34; 95% CI 1.03-1.75) and fever (RR = 1.54; 95% CI 1.33-1.80). The estimated incidence of RSV-ARI and RSV-LRTI, per 100,000 child years, among those aged <5 years was 767 and 283, respectively. Conclusion The burden of childhood RSV-associated URTI and LRTI presenting to outpatients in this setting is considerable. The clinical features of cases associated with an RSV infection were more severe than cases without an RSV diagnosis.